Features of carcass performance and characteristics and meat quality in pigs fed agave oligofructans - Sánchez Chiprés, D.; Leal, E.; Galindo, J.; Valdovinos, M. A.; Ly, J. (Cuban Journal of Agricultural Science, 2018)
A total of 84 Yorkshire x Landrace x Duroc pigs, female and castrated male in the same proportion, were used. These animals were housed in groups of two, to be randomly assigned to three treatments that consisted in the addition of 0, 2.5 and 5.0 g of agave oligofructans (Agave tequilana) per kilogram of diet. Animals were fed ad libitum with a diet of cereals and grains from 28 d of age, with an initial weight of around 7 kg. There was no significant effect (P>0.05) in any measure for sex x oligofructan level interaction. Oligofructans determined a lower food intake (P<0.001), but there was no effect of treatment on weight gain, thus food conversion also decreased (P = 0.09). Oligofructans determined the lowest numeric values, without significant effect (P > 0.05) for thickness of dorsal fat, and the highest for lean yield, regarding control treatment and significantly (P < 0.001) lower for losses by leaking and for pH at 24 h. It is suggested that agave oligofructans may have a positive influence on carcass and meat characteristics of growing finishing pigs, with more marked effect than in performance traits. Key words: pigs, agave, prebiotics, zootechnics, lipid metabolism